The color in Mahmoud Sami Al-Baroudi’s poetry - Issa, Magda (Al-Adab Journal, 2023)
This research aims to study the color in the poetry of the Arab poet Mahmoud Sami Al-baroudi considering color as one of the elements of the artistic image taking from the poet’s office as a model for this study. These colors are white. Black، and red، and the use of other colors in his poetry، which are blue، green and yellow، as well as the multiple connotations that enriched the poetic text and revealed more psychological idea and artistic gifts in the poet’s poetry in an attempt to reveal its artistic value and aesthetic significance. In this research and study، we shed light on the importance of role of colors to be an essential tool in revealing the axis of artistic beauty in the literary text.